Restoring truth: The biblical homily role amidst pragmatic challenges of congregation life - Julius Stefanus Sibagariang (Institut Agama Kristen Negeri Toraja, 2025)
Homilies in the Church cannot be separated from the concrete challenges faced in the life of the congregation. One of the major challenges confronting contemporary homiletics is the growing dominance of pragmatism in congregational life, where preaching is often expected to address immediate needs, interests, and practical concerns rather than to proclaim biblical truth. In such a context, the congregation tends to evaluate homilies based on their usefulness or relevance to daily life, rather than their faithfulness to the truth of God’s Word. This tendency risks reducing biblical homilies to motivational or problem-solving speeches, thereby weakening their theological depth. This article aims to analyze how pragmatic orientations influence the reception and content of homilies within congregational life and to explore ways in which homiletic practice can respond critically to these challenges. Drawing on biblical foundations and Pauline homiletic perspectives, the study seeks to restore the essential role of homilies as faithful proclamations of divine truth. Ultimately, this article contributes to contemporary homiletic discourse by offering theological and practical insights to ensure that biblical and Pauline homilies remain rooted in God’s truth while engaging meaningfully with the real-life challenges of the congregation.